A COMPARATIVE STUDY BETWEEN KOREAN AND JAVANESE QUANTIFIER AND THE APPLICATION IN SENTENCES - Mukaromah, Dyah (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2019)
Abstract? A language without grammar is a body without soul. Grammar truly holds an essential part in a language. In grammar, there is one important part which is said to be quantifier. Quantifier is specific words used to count numbers of an object. Such as found in the phrases, two pages letter, three bars of chocolate, etc. Quantifier is widely used in plenty languages, yet not all languages. There are several languages which do not recognise the system of counting object using quantifier. Those languages only use substitute words having the same function as quantifier. This paper explain a comparative study between language which use quantifier (in this case Korean) and language which do not use quantifier (Javanese), yet use substitute words instead. The differences then compared in the view of how it is applied in the sentences in each language.